Association of Killer Cell Immunoglobulin-Like Receptor Genes with the Graft versus Host Disease after Related Haematopoietic Stem Cell Transplantation in Patients with Haematological Malignancies from Republic of Macedonia - Aleksandar Petlichkovski; Zlate Stojanoski; Eli Djulejic; Borce Georgievski; Mirko Spiroski (My University, 2012)
Aim: The aim of this study was to examine the gene frequencies of 16 KIR genes and pseudogenes and KIR genotypes in Macedonian patients with transplanted bone marrow and their sibling donors in treatment of haematological malignancy, and to analyse eventual association of the gene content with the occurrence of a graft versus host disease (GVHD). Material and Methods: The study was performed on 24 patients and their HLA-matched sibling donors. Results: Comparison of KIR gene frequencies between the total 24 donors and healthy Macedonians reveals statistically significant difference for KIR2DS1 (F= 0.481 in the controls group, and 0.76 in the patients group, p=0.004). This significance is even higher when the frequency of KIR2DS1 in controls is compared with the frequency in donors from pairs with GVHD (F= 0.923, P= 0.002). Another significant difference was observed for the frequency of the full-length allele of KIR2DS4*001-002, present in 25.2% of the control individuals, but in as much as 81.8% of the recipients of haematopoietic stem cell (P=0.0005). We did not see any statistically significant difference in distribution of the C1/C1, C1/C2 and C2/C2 groups among GVHD pairs. Conclusion: Our results address the difference between the haematopoietic stem cell transplantation settings with sibling and unrelated donors and suggest that the KIR2DS4*001/002 might be a predisposing factor for severe GVHD in sibling HSCT.
Keywords: KIR genes; Graft versus host disease